2018
DOI: 10.24114/gr.v7i2.11551
|View full text |Cite
|
Sign up to set email alerts
|

Pelaksanaanpembelajaran Berbasispendekatansaintifik Pada Mata Pelajaran Seni Budaya Materi Seni Rupadi SMPN Bukittinggi

Abstract: AbstrakPenelitian ini bertujuan untuk memperoleh gambaran tentang  pelaksanaan pembelajaran seni budaya materi seni rupa berbasis  pendekatan saintifik di SMP  Bukittinggi. Metode yang  digunakan  dalam  penelitian  ini  adalah  metode  deskriptif  kualitatif. Subjekdalampenelitianiniadalahguru seni budaya di SMP Kota Bukittinggi. Teknik pengumpulan dat amenggunakan teknik observasi, wawancara, dan dokumentasi. Instrumen penelitian yang digunakan yaitu pedoman observasi dan pedoman wawancara.Teknik analisis da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Second, the validation results of the lesson plan seen from the component formulation aspect reached 87.5% and it was categorized as a very valid product. The component of learning steps like main activities in learning indicated that the lesson plan was designed according to scientific-based approach (Wisdiarman, et al, 2018). Furthermore, the formulation of main activities in the lesson plan had followed the steps of the scientific approach such as observing, questioning, gathering information, associating, and communicating.…”
Section: B the Validity Of The Lesson Planmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the validation results of the lesson plan seen from the component formulation aspect reached 87.5% and it was categorized as a very valid product. The component of learning steps like main activities in learning indicated that the lesson plan was designed according to scientific-based approach (Wisdiarman, et al, 2018). Furthermore, the formulation of main activities in the lesson plan had followed the steps of the scientific approach such as observing, questioning, gathering information, associating, and communicating.…”
Section: B the Validity Of The Lesson Planmentioning
confidence: 99%
“…They never use such approach. Though, this approach has succeeded in improving learning outcomes (Marjan, et al, 2014;Hala, et al, 2015;Diani, et al, 2016;Wisdiarman, et al, 2018) Besides, some researches hypothesized that scientific-based learning approach can improve students' learning outcome in some courses like craft. However, some problems such as the availability of a students' worksheet provided by craft teachers associations, educational office, commercial products are very rare.…”
Section: Introductionmentioning
confidence: 99%